Construction method and application of magnetic relaxation switch sensor

The sodium alginate-carboxymethyl chitosan hydrogel-based magnetic relaxation switch sensor addresses instability issues in traditional MRS sensors by using pH-mediated swelling and antigen-antibody binding, achieving enhanced sensitivity and stability for cadmium ion detection.

CN119164994APending Publication Date: 2024-12-20CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411233877.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Traditional magnetic relaxation switch (MRS) sensors face challenges with the instability of magnetic nanoparticle aggregation and non-specific valence changes due to external magnetic fields, affecting their sensitivity and stability in detecting target substances.

Method used

A magnetic relaxation switch sensor is constructed using sodium alginate-carboxymethyl chitosan hydrogel, which is non-magnetic and stable under magnetic fields, utilizing pH-mediated hydrogel swelling and antigen-antibody binding to enhance sensitivity and stability.

Benefits of technology

The sensor achieves stable and sensitive detection of cadmium ions with a linear range of 0.01-10 ng/mL and a detection limit of 0.006 ng/mL, improving upon traditional MRS sensors by reducing non-specific aggregation and environmental interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119164994A_ABST
    Figure CN119164994A_ABST
Patent Text Reader

Abstract

The invention relates to the field of magnetic resonance sensors, in particular to a construction method and application of a magnetic relaxation switch sensor. The magnetic relaxation switch sensor comprises sodium alginate carboxymethyl chitosan hydrogel, a cadmium ion specific antigen, a cadmium ion specific antibody, an alkaline phosphatase labeled secondary antibody and 2-phosphoric acid-1-sodium ascorbate. The MRS sensor capable of stably and sensitively detecting Cd < 2 + > is constructed through the sodium alginate-carboxymethyl chitosan hydrogel, and the problem that the MRS sensor is insufficient in stability and sensitivity in detection is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of magnetic resonance sensors, and in particular to a construction method and application of a magnetic relaxation switch sensor. Background Art

[0002] In recent years, magnetic relaxation switching (MRS) has attracted much attention and has been widely used in the field of modern analysis for detecting a variety of target substances, such as proteins, viruses, heavy metals, pesticides and toxins. However, traditional magnetic relaxation switch sensors usually use the state changes of magnetic nanoparticles (MNPs) and the valence changes of paramagnetic nanoparticles to mediate the changes in relaxation time. They are easy to aggregate under magnetic field conditions and are easily affected by the external environment, which limits the stability of traditional MRS biosensors. In order to meet this challenge, many researchers have made a lot of efforts in recent years. For example, optimizing experimental conditions, combining click chemistry reactions and polydopamine-mediated signal conversion systems to improve the stability and sensitivity of sensors, etc. Although higher stability has been achieved, due to the inherent magnetism of magnetic nanomaterials, it still cannot avoid the non-specific aggregation of magnetic nanoparticles under external magnetic field conditions, and paramagnetic iron or manganese ions cannot avoid the non-specific valence changes caused by the environment. Therefore, MRS sensors based on transverse relaxation time signals still have some challenges in improving the sensitivity and stability of MRS biosensors.

[0003] In traditional magnetic relaxation switches, superparamagnetic nanomaterials are usually aggregated or dispersed by the target. Such superparamagnetic nanomaterials have strong magnetic susceptibility and strong magnetism in the presence of an external magnetic field. Traditional MRS sensors based on superparamagnetic nanoparticle assembly / dispersion have unstable aggregation / dispersion of MNPs themselves and non-specific aggregation of MNPs caused by external magnetic fields, which impairs the detection stability of MRS sensors. In addition, when the valence state change of paramagnetic materials is detected by the target, it is easily affected by external environmental conditions to cause non-specific valence state changes, resulting in poor sensor stability. Therefore, it is crucial to continue to develop a highly stable material for constructing MRS sensors to improve the stability of the sensor. Summary of the invention

[0004] The present invention constructs a method for stably and sensitively detecting Cd by using sodium alginate-carboxymethyl chitosan (SA-CMCS) hydrogel. 2+The invention prepares sodium alginate-carboxymethyl chitosan hydrogel beads by physical crosslinking method, and constructs a magnetic relaxation sensor (Gel-MRS) based on pH-mediated hydrogel swelling to improve the stability and sensitivity of magnetic relaxation switch sensor, based on the fact that the gel itself is non-magnetic and not easily affected by the magnetic field.

[0005] A magnetic relaxation switch sensor comprises sodium alginate carboxymethyl chitosan hydrogel, cadmium ion specific antigen, cadmium ion specific antibody, alkaline phosphatase-labeled secondary antibody, and 2-phospho-l-ascorbic acid trisodium salt.

[0006] Preferably, the sodium alginate carboxymethyl chitosan hydrogel is prepared from sodium alginate and carboxymethyl chitosan in a mass ratio of (1.5-4): 1, more preferably in a mass ratio of 2: 1. Studies have shown that the stability and sensitivity of the magnetic relaxation switch sensor can be significantly improved within this ratio range.

[0007] Preferably, the crosslinking agent for preparing the sodium alginate carboxymethyl chitosan hydrogel is calcium chloride. Studies have found that compared with citric acid, calcium chloride can steadily increase the melt expansion rate with the increase of pH, thereby obtaining a better crosslinking effect.

[0008] Preferably, the sodium alginate is high-viscosity sodium alginate.

[0009] In some specific embodiments, the ratio of the comonomers β-d-manuronic acid (M) and α-l-guluronic acid (G) of the sodium alginate is (1:1)-(1:2), more preferably 1:2.

[0010] Studies have shown that sodium alginate carboxymethyl chitosan hydrogel prepared with high-viscosity sodium alginate as raw material has better stability and mechanical properties, and can firmly lock internal moisture, making the T2 measurement value (hydrogen proton transverse relaxation time) more reliable.

[0011] In the present invention, the sodium alginate carboxymethyl chitosan hydrogel can be prepared according to existing methods, such as physical cross-linking method, and the present invention is not particularly limited.

[0012] In some specific embodiments, the preparation method of the sodium alginate carboxymethyl chitosan hydrogel comprises:

[0013] dissolving sodium alginate and carboxymethyl chitosan in water to obtain a blend;

[0014] The blend is added into a calcium chloride solution and cross-linked to obtain the sodium alginate carboxymethyl chitosan hydrogel.

[0015] In some embodiments, the concentration of sodium alginate in the blend is 1.5%-4.0% (w / v), and the concentration of carboxymethyl chitosan is 1.0% (w / v).

[0016] In some embodiments, the preparation method of the sodium alginate carboxymethyl chitosan hydrogel comprises the following steps: First, carboxymethyl chitosan (CMCS) and sodium alginate (SA) are dissolved in deionized water at a ratio of 1% and 2% (w / v), respectively. Then, the mixture is ultrasonically treated to remove trapped bubbles. Under slow stirring, the sodium alginate carboxymethyl chitosan (SA-CMCS) mixture is dripped into a calcium chloride solution (1% w / w, 80 mL) using a pump (flow rate: 1 mL / min) and a 10 ml sterile syringe. The cross-linking reaction is carried out at room temperature for 1 h to obtain sodium alginate carboxymethyl chitosan (SA / CMCS) hydrogel beads.

[0017] In some embodiments, the step of freeze-drying the sodium alginate carboxymethyl chitosan hydrogel is also included.

[0018] The sodium alginate carboxymethyl chitosan hydrogel of the present invention has uniform size and good relaxation performance. The transverse relaxation performance of protons in the material is crucial to whether a magnetic relaxation switch sensor can be successfully constructed. Materials with greater relaxation are more likely to be detected as signals, and the viscosity of the hydrogel affects the state of water molecules in the hydrogel. After the viscosity of the hydrogel is enhanced by adding carboxymethyl chitosan, the T2 change and relaxation rate of the hydrogel beads are higher, which is beneficial to the relaxation performance and stability of the hydrogel.

[0019] The present invention constructs a pH-mediated magnetic relaxation switch sensor, utilizes antigen-antibody specific binding, uses alkaline phosphatase (ALP) to mediate alginate expansion through competitive immune reaction, and establishes a linear relationship between the target concentration and the longitudinal relaxation time signal, thereby achieving stable, sensitive and simple detection of the target. This invention belongs to the field of detection technology and is applicable to the field of food safety and Cd in rice, drinking water, etc. 2+ Detection.

[0020] The present invention also provides a method for constructing the magnetic relaxation switch sensor, comprising:

[0021] Providing sodium alginate carboxymethyl chitosan hydrogel;

[0022] The sodium alginate carboxymethyl chitosan hydrogel, cadmium ion specific antigen, cadmium ion specific antibody, alkaline phosphatase labeled secondary antibody, and 2-phospho-l-ascorbic acid trisodium salt are mixed to obtain a magnetic relaxation switch sensor.

[0023] In some specific embodiments, the construction method further comprises the step of blocking the cadmium ion-specific antigen with bovine serum albumin (BSA) in advance.

[0024] In some specific embodiments, the construction method includes: adding a cadmium ion-specific antigen (preferably at a concentration of 4 μg / mL) to a cell culture plate (e.g., a 96-well plate), incubating overnight at 37°C, and washing with a PBST washing solution to remove unbound substances; blocking with a phosphate buffer containing 1% bovine serum albumin, and then incubating in an incubator at 37°C (e.g., 2 hours); washing again with a PBST washing solution; adding a cadmium ion-specific antibody (preferably at a concentration of 4 μg / mL), incubating at 37°C (e.g., 30 minutes), and then washing with a PBST washing solution; adding an alkaline phosphatase-labeled secondary antibody solution, incubating at 37°C (e.g., 30 minutes), and washing with a PBST washing solution; adding 150 μL of a 2-phospho-L-ascorbic acid trisodium salt solution, placing at room temperature (e.g., 15 minutes), and then adding the sodium alginate carboxymethyl chitosan gel beads, and incubating (preferably 180 minutes) to obtain a magnetic relaxation switch sensor.

[0025] The present invention also includes application of the magnetic relaxation switch sensor in cadmium ion detection.

[0026] The present invention also provides a method for detecting cadmium ions (Cd 2+ ) methods, including:

[0027] The nuclear magnetic resonance imaging analysis method is used to detect and obtain the hydrogen proton transverse relaxation time T2 of the sodium alginate carboxymethyl chitosan hydrogel when no sample to be tested is added;

[0028] The magnetic relaxation switch sensor is mixed with a sample to be tested; and a nuclear magnetic resonance imaging analysis method is used to detect and obtain the hydrogen proton transverse relaxation time T2' of the sodium alginate carboxymethyl chitosan hydrogel at this time;

[0029] According to the formula ΔT2=T2'-T2, ΔT2 is obtained;

[0030] The cadmium ion concentration in the sample to be tested is obtained according to ΔT2 and the standard curve.

[0031] Specifically, the method for detecting cadmium ions also includes the step of preparing a standard curve.

[0032] Specifically, a nuclear magnetic resonance imaging analyzer (NMR) can be used to perform nuclear magnetic resonance imaging analysis and detection.

[0033] Beneficial Effects

[0034] (1) The present invention prepares SA / CMCS hydrogel beads through a physical cross-linking procedure, with high swelling rate and good relaxation performance. By utilizing antigen-antibody specific binding, alkaline phosphatase (ALP) is used to mediate alginate swelling through competitive immune response, and the ALP system is used to mediate pH, thereby regulating the swelling of the hydrogel beads. The present invention can provide data support for solving the problem of insufficient stability of MRS sensors.

[0035] (2) The present invention constructs a magnetic relaxation switch sensor based on pH-driven high-stability hydrogel, which does not require complicated sample pretreatment steps and is easy to operate. Its linear range is 0.01-10 ng mL -1 , the detection limit is as low as 0.006ng mL -1 The detection sensitivity of the established Gel-MRS sensor was significantly higher than that of the traditional MRS sensor (0.45 ng mL -1 ). By detecting Cd in rice samples 2+ The present invention can construct a method for stably and sensitively detecting Cd in rice samples. 2+ The MRS sensor solves the problem of insufficient stability in detection of MRS sensors based on aggregation or dispersion of superparamagnetic nanomaterials. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a schematic diagram of the preparation method of sodium alginate carboxymethyl chitosan hydrogel according to an embodiment of the present invention, and a schematic diagram of the construction method and detection principle of a magnetic relaxation switch sensor.

[0037] Figure 2 This is the characterization result of the hydrogel in Experimental Example 1 of the present invention.

[0038] Figure 3 This is the swelling dynamics result of the hydrogel in Experimental Example 1 of the present invention.

[0039] Figure 4 This is the selection and optimization result of the cross-linking agent in Experimental Example 1 of the present invention.

[0040] Figure 5 The apparent morphology and size distribution results of the gel beads in Experimental Example 1 of the present invention.

[0041] Figure 6 ΔT2 of hydrogel beads with different sodium alginate concentrations in Experimental Example 1 of the present invention.

[0042] Figure 7 This is the stability analysis result of the gel bead T2 signal in Experimental Example 1 of the present invention.

[0043] Figure 8This is the effect of incubation time and antigen / antibody / concentration on the relaxation sensing system in Experiment 2 of the present invention.

[0044] Fig. 9 This is the LF-NMR of the hydrogel beads swollen at different pH values ​​in Experiment 3 of the present invention.

[0045] Fig.10 The results of specificity and stability analysis of Experiment 4 of the present invention and the cadmium ion standard curve of Example 3 are shown. DETAILED DESCRIPTION

[0046] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.

[0047] In order to solve the problem of insufficient stability of traditional MRS sensors in detection and improve the stability of magnetic relaxation switch sensors, the present invention mediates the rapid expansion of hydrogels through pH. This expansion state can cause changes in the size of the hydrogel network gaps, allowing the absorption of a large amount of water without dissolving. At this time, water molecules are fixed inside the gel gaps, reducing the degree of freedom of water protons, thereby causing changes in the water molecule relaxation signal. A relationship is established between the change in the relaxation signal and T2 (hydrogen proton transverse relaxation time). Since the hydrogel has the advantages of stable structure, non-magnetic properties, internal porous structure and high water content, it will not be affected by the external magnetic field, thereby improving the stability of the magnetic relaxation switch sensor.

[0048] The present invention provides a simple and reliable method, i.e., using alkaline phosphatase (ALP) to mediate alginate swelling for MRS. When the target is not present, the alkaline phosphatase-labeled secondary antibody binds to the antibody, and the ALP can remove the phosphate group in 2-phospho-L-ascorbic acid (AAP) to generate ascorbic acid (AA), which easily ionizes H+ and reduces the pH of the solution. Sodium alginate contains a large number of carboxyl groups. When the pH of the solution is acidic, the high concentration of hydrogen ions inhibits the dissociation of the carboxyl groups, and the molecular chains containing carboxyl groups gather together due to the presence of hydrogen bonds inside. Therefore, the sodium alginate network structure cross-linked by calcium ions shrinks, the water molecules are outside the hydrogel, and T2 is large. When the target is present, the target binds to the antibody, the alkaline phosphatase is washed, the pH is high, the molecular chains containing carboxyl groups are gradually stretched, and the corresponding three-dimensional network expands. By locking the water molecules in the "egg box" network structure of the alginate hydrogel, the lateral relaxation of water protons in the aqueous solution can be significantly changed, resulting in a decrease in the T2 value.

[0049] Herein, sodium alginate carboxymethyl chitosan hydrogel is sometimes referred to as hydrogel beads or SA / CMCS hydrogel beads.

[0050] In some cases, the sodium alginate carboxymethyl chitosan hydrogels were washed several times with deionized water and then freeze-dried before further analysis.

[0051] Detection Methods

[0052] (1) Detection method of pH response of hydrogel beads:

[0053] The freeze-dried hydrogel beads were immersed in 30 mL of different pH buffers (pH = 3.0, 4.0, 5.0, 6.0, 7.0, 8.0) to measure the pH swelling rate of the hydrogel beads. SR ) is calculated as follows:

[0054] W SR =(W1-W0) / W0*100%

[0055] Where W SR is the swelling ratio of SA / CMCS hydrogel beads in different pH buffers, W1 is the weight of SA / CMCS hydrogel beads, and W0 is the initial weight of SA / CMCS hydrogel beads.

[0056] (2) Morphological determination of hydrogel beads: The average size of wet and dry hydrogel beads (n=300) was manually analyzed using a vernier caliper.

[0057] (3) Dynamic rheological analysis method: Rheological measurements were performed using a rotational rheometer (HAAKE MARS60) at 25°C. The rheological experiments were performed at a fixed strain of 25°C, and the storage modulus (G′) and loss modulus (G″) of SA / CMCS were measured by frequency scanning in the frequency range of 0.1 to 10 Hz.

[0058] (4) Magnetic resonance imaging analyzer relaxation detection method:

[0059] ①Use oil sample to calibrate instrument parameters.

[0060] ②Change the queue name to Q-CPMG and adjust the series parameters.

[0061] ③The Carr–Purcell–Meiboom–Gill (CPMG) sequence pulse sequence was used for T2 measurement, and its parameters were set as follows: repetition time (ms): 7000; echo time (ms): 0.3; digital gain: 3; number of echoes: 20000; sampling frequency: 100 KHz; accumulation times: 16; and RF delay: 0.08.

[0062] ④The magnet coil is NMI20-15 mm.

[0063] ⑤Put the sample to be tested into the NMR tube and start sampling.

[0064] ⑥ After the sample is collected, select the single component inversion data. After the inversion is completed, the required transverse relaxation time can be obtained, and the data can be sorted, processed and analyzed.

[0065] ⑦T2 value and Cd 2+ The relationship between the concentrations can be used for Cd 2+ Quantitative analysis of .

[0066] The main reagents used are as follows:

[0067] Reagent name Manufacturer <![CDATA[Sodium alginate ((C6H7NaO6) n M:G = 1:2)]]> Shanghai MacLean Biochemical Technology Co., Ltd. <![CDATA[Sodium alginate ((C6H7NaO6) n M:G = 2:1)]]> Shanghai MacLean Biochemical Technology Co., Ltd. <![CDATA[Carboxymethyl chitosan (FeCl3·6H2O)]]> Beijing Bailingwei Technology Co., Ltd. Cadmium ion specific antigen (2 μg / mL) Wuxi Lvkang Co., Ltd. Cadmium ion specific antibody (4 μg / mL) Wuxi Lvkang Co., Ltd. Alkaline phosphatase conjugated secondary antibody solution Shanghai MacLean Biochemical Technology Co., Ltd. 2-Phospho-L-ascorbic acid trisodium salt solution Shanghai MacLean Biochemical Technology Co., Ltd.

[0068] The main instruments used are as follows:

[0069] Instrument Type Manufacturer NMI-20-CA Magnetic Resonance Imaging Analyzer Suzhou Newmai Electronic Technology Co., Ltd. Fourier Transform Infrared Spectrometer Thermo Nicolet 670 Company RH basic2 vortex shaker IKA Germany JEOL JEM-2100 Transmission Electron Microscope JEOL Ltd.

[0070] Chinese and English comparison:

[0071]

[0072]

[0073]

[0074] Example 1

[0075] This embodiment provides sodium alginate carboxymethyl chitosan hydrogel, and the preparation method thereof is as follows:

[0076] Carboxymethyl chitosan (CMCS) and sodium alginate (SA) were dissolved in deionized water at a concentration of 1% and 2% (w / v), respectively. Then, the mixture was ultrasonically treated to remove bubbles. The obtained sodium alginate carboxymethyl chitosan (SA-CMCS) blend was further slowly dripped into a CaCl2 solution (1% w / w, 80 mL) through a syringe pump (flow rate: 1 mL / min) and a 10 mL sterile syringe. The cross-linking reaction was carried out at room temperature for 6 h to obtain sodium alginate carboxymethyl chitosan hydrogel beads (SA / CMCS).

[0077] The sodium alginate carboxymethyl chitosan hydrogel prepared in this example is sometimes also referred to as high viscosity hydrogel beads (HVB).

[0078] In this embodiment, the ratio of the comonomers β-d-manuronic acid (M) and α-l-guluronic acid (G) of the sodium alginate is 1:2.

[0079] The preparation method of sodium alginate carboxymethyl chitosan hydrogel in this embodiment can be found in Figure 1 A.

[0080] Example 2

[0081] This embodiment provides a magnetic relaxation switch sensor (Gel-MRS sensor), and its construction method adopts the immune competition method, which is as follows:

[0082] Add 100 μL of cadmium ion-specific antigen (2 μg / mL) to each well of a 96-well plate, incubate in a 37°C incubator overnight, wash three times with PBST washing solution (phosphate buffered saline containing Tween-20 washing solution) to remove unbound substances; block with 1% bovine serum albumin (BSA) in phosphate buffered saline (PBS) solution, and incubate in a 37°C incubator for 2 h. The wells were washed three times again with PBST washing solution; 50 μL of cadmium ion-specific antibody (4 μg / mL) was added to each well, incubated at 37°C for 30 min, and then washed three times with PBST washing solution; 20 μL of alkaline phosphatase-labeled secondary antibody solution was added to each well, incubated at 37°C for 30 min, and washed three times with PBST washing solution; 150 μL of 2-phospho-L-ascorbic acid trisodium salt solution was added to each well, and after standing at room temperature for 15 min, the sodium alginate carboxymethyl chitosan gel beads prepared in Example 1 were added and incubated for 180 min to obtain a magnetic relaxation switch sensor (Gel-MRS magnetic relaxation switch sensor).

[0083] The construction method and detection principle of the magnetic relaxation switch sensor of this embodiment can be found in Figure 1 b and c.

[0084] Example 3

[0085] The Gel-MRS magnetic relaxation switch sensor constructed in Example 2 was used to detect Cd in rice. 2+ .

[0086] Cd 2+ It is a typical heavy metal ion. Long-term exposure to Cd 2+ Severely polluted areas can induce growth defects, osteoporosis, cortical fractures, sclerosis and cystic changes in wild rabbits. The International Agency for Research on Cancer (ICRA) has listed it as a carcinogen. Rice is considered one of the main sources of cadmium exposure in the diet. Currently, high concentrations of toxic heavy metals Cd in rice soils are 2+ Its accumulation in rice and food chain is a global problem, which seriously endangers human health. 2+ This embodiment uses a pH-driven high-stability hydrogel magnetic relaxation switch sensor to detect Cd in rice. 2+ .

[0087] (1) Establishment of cadmium ion standard curve

[0088] Performed in 96-well plates.

[0089] 1. Add 100 μL of cadmium ion-specific antigen (2 μg / mL) to each well, incubate overnight at 37°C, and wash three times with PBST washing solution to remove unbound substances;

[0090] 2. Block the wells with 1% bovine serum albumin (BSA) in phosphate buffered saline (PBS) solution and incubate them in a 37°C incubator for 2 hours. Wash the wells three times with PBST washing solution;

[0091] 3. Add 50 μL of cadmium ion-specific antibody (4 μg / mL) and 50 μL of different concentrations of Cd 2+ The standard solution (concentrations were 0.001, 0.005, 0.01, 0.02, 0.05, 0.1, 0.2, 0.5, 1, 2, 5, 10, 100, and 1000 ng / mL, respectively) was incubated at 37°C for 30 min, followed by three washes with PBST;

[0092] 4. Add 20 μL of alkaline phosphatase-labeled secondary antibody solution to each well, incubate at 37°C for 30 min, and wash three times with PBST washing solution;

[0093] 5. Add 150 μL of 2-phospho-L-ascorbic acid trisodium salt solution to each well, place at room temperature for 15 min, then add the sodium alginate carboxymethyl chitosan gel beads prepared in Example 1, incubate for 180 min, and use a 0.5T nuclear magnetic resonance imaging analyzer (NMR) instrument to detect the T2 value of the sample at room temperature.

[0094] ΔT2 is calculated as follows: ΔT2 = T2' - T2; where T2' is the 2+ The relaxation time of the test solution with a concentration of Cd2 is 1, while T2 is the relaxation time of the blank sample test. The LOD calculation formula is LOD = 3S / M, where S represents the standard deviation of the blank sample and M represents the slope of the standard curve in the low concentration range. 2+ The logarithm of the standard sample concentration is used as the horizontal axis, and ΔT2 is used as the vertical axis to obtain the following Fig.10 The standard curve shown in b shows the Cd 2+ Relationship between concentration and △T2. Fig.10 The results in b show that △T2 and Cd 2+ In the concentration range of 0.01-5 ng / mL, the relationship is linear: y=92.87lg(x)+237.73, R 2 =0.98127. The LOD of the detection system can reach 0.009 ng / mL, and the detection effect is good.

[0095] (2) Actual sample testing

[0096] ①Pretreatment of actual samples

[0097] Rice was purchased from a local retailer, ground into powder, and 5 g of rice powder was added to a 10 mL methanol / water (volume ratio of 70:30) mixed solution. After gentle stirring for 1 h and ultrasonication for 20 min, the extract of the rice sample was centrifuged for 5 min at 6000 rpm, and the supernatant was diluted 10 times with 0.01 mM Pb buffer (pH = 7.4) to obtain a rice sample solution, which was stored at 4 ° C for further use. Among them, the rice sample solution is the sample studied.

[0098] ② Cd in actual samples 2+ Detection

[0099] The rice sample liquid is used as a sample and is tested according to the method for establishing the above-mentioned cadmium ion standard curve. That is, the nuclear magnetic resonance imaging analysis method is used for detection to obtain the hydrogen proton transverse relaxation time T2 of the sodium alginate carboxymethyl chitosan hydrogel when no sample to be tested is added; the magnetic relaxation switch sensor is mixed with the sample to be tested; the nuclear magnetic resonance imaging analysis method is used for detection to obtain the hydrogen proton transverse relaxation time T2' of the sodium alginate carboxymethyl chitosan hydrogel at this time; according to the formula ΔT2=T2'-T2, ΔT2 is obtained; according to ΔT2 and the standard curve, the cadmium ion concentration in the sample to be tested is obtained.

[0100] To detect Cd in rice sample solution 2+ Each time, 150 μL of rice sample solution was taken. Next, T2 measurement was performed using a low-field nuclear magnetic resonance instrument. The test was performed at least three times to ensure the reliability of the data. 2+ The three different concentrations of Cd were spiked into food samples and the recovery rate was tested. 2+ Add rice sample solution for experimental operation, Cd 2+ The final concentration was 20 pg mL -1 , 50pg mL -1 and 100 pg mL -1 , the measured average T2 value was substituted into the dose response equation of the sensor and the sample recovery rate was calculated.

[0101] The results showed that Cd was not detected in commercially available rice samples. 2+ The recoveries were 99.39% to 112.83% (Table 1), and the relative standard deviations (RSDs) were 4.56% to 13.8%. In the spiked experiments, the high recoveries and low RSDs indicated that Gel-MRS was suitable for detecting Cd in real samples. 2+ It has great potential and stability.

[0102] Table 1 Cd in rice samples 2+ Determination of

[0103]

[0104] In Table 1, MRS is the method of this embodiment, and AAS is the national standard method (GB5009.15-2014, National Food Safety Standard Determination of Cadmium in Food).

[0105] Compared with other common detection methods, this embodiment has good detection sensitivity, see Table 2.

[0106] Table 2 Comparison of detection performance of Gel-MRS sensor and other detection methods

[0107] Sensor or detection type Linear range Detection limit literature Electrochemical Sensors 0.5–50 μg / L 0.23 μg / L [1] Colorimetry 1-500ng / mL 0.7 ng / mL [2] Surface Plasmon Resonance 0-1000ng / mL 1.25 ng / mL [3] Traditional-MRS 0.5–50 ng / mL 0.16ng / mL [4] Immunoassay 0.03-1.11 ng / mL 0.15ng / mL [5] UV spectrophotometry <![CDATA[8-100μg / L / ]]> 1.74 μg / L [6] Gel-MRS 0.010-5ng / mL 0.009ng / mL The method of this embodiment

[0108] [1]Yin FQ, Mo YL, Liu XT, et al. An ultra-sensitive and selective electrochemical sensor based on GOCS composite and ion imprinted polymer for the rapid detection of Cd 2+ in food samples[J].Food Chemistry,2023,410.

[0109] [2]Tao Z, Wei L, Wu S, et al. A colorimetric aptamer-based method for detection of cadmium using the enhanced peroxidase-like activity of Au–MoS2nanocomposites[J]. Analytical Biochemistry, 2020, 608: 113844.

[0110] [3]Kang GF, Wang YZ, Bai YF, et al.Surface plasmon resonance basedcompetitive immunoassay for Cd 2+ [J].RSC Advances,2017,7(70):44054-44058.

[0111] [4]Xu Z, Li Q, Wang Y, et al. Target-triggered UCNPs / Fe3O4@PCN-224 assembly for the detection of cadmium ions by upconversion fluorescence and magneticrelaxation switch dual-mode immunosensor[J]. Sensors and Actuators B: Chemical, 2023,377:133037.

[0112] [5]Ling S, Zhao Q, Iqbal MN, et al. Development of immunoassay methods based on monoclonal antibody and its application in the determination of cadmium ion[J]. Journal of Hazardous Materials, 2021,411:124992.

[0113] [6]Qi D, Zhang H, Zhou Z, et al. Cadmium ion-imprinted polymers for adsorption and detection of cadmium ions[J]. Journal of Environmental Chemical Engineering, 2023, 11(5):110804.

[0114] Comparative Example 1

[0115] The only difference from Example 1 is that carboxymethyl chitosan (CMCS) is omitted and only sodium alginate (SA) is used to prepare the hydrogel (SA hydrogel for short).

[0116] The sodium alginate carboxymethyl chitosan hydrogel prepared in this comparative example is sometimes also referred to as low viscosity hydrogel beads (LVB).

[0117] Experiment 1 Optimization of preparation conditions of sodium alginate carboxymethyl chitosan gel beads

[0118] (1) Whether to add carboxymethyl chitosan

[0119] Materials with greater relaxation are more likely to be detected. This experiment compared the relaxation time and relaxation rate before and after the addition of carboxymethyl chitosan. The transverse relaxation performance of the proton of the material is crucial to the successful construction of the magnetic relaxation switch sensor. The detection method is the same as in Example 3.

[0120] Figure 2 a represents the changes in relaxation rate and T2 of hydrogel beads before and after the addition of CMCS. Figure 2 In a, SA represents the magnetic relaxation switch sensor constructed with the SA hydrogel of Comparative Example 1; SA+CMCS represents the magnetic relaxation switch sensor constructed with the hydrogel of Example 1.

[0121] like Figure 2 As shown in a, under the same conditions, the T2 change and relaxation rate of the hydrogel beads were higher after the addition of carboxymethyl chitosan. This indicates that the addition of carboxymethyl chitosan not only has stronger structural stability but also has superior relaxation properties.

[0122] (2) Viscosity of sodium alginate

[0123] Take the hydrogels of Example 1 (sodium alginate with high viscosity, M:G=1:2) and Comparative Example 1 (sodium alginate with low viscosity, M:G=2:1), compare the swelling rates of the two gels, compare their relaxation properties by low-field nuclear magnetic resonance, and measure the loss modulus and storage modulus by rheometer, and compare the materials with high swelling rate, good relaxation property and high storage modulus. Finally, optimize the concentration of sodium alginate. Perform performance characterization and related tests (mechanical strength, swelling capacity, relaxation rate and swelling kinetics of hydrogel) on the obtained gel beads. The test results are as follows: Figure 2 As shown in b, c and d.

[0124] from Figure 2 It can be seen from b that the relaxation rate of high viscosity hydrogel is significantly higher than that of low viscosity, which may be because the compact structure can provide more water-capturing space for the hydrogel beads and thus obtain a higher relaxation rate.

[0125] pH responsiveness and mechanism analysis of gel beads: The gel beads were placed in buffer solutions of different pH (3, 4, 5, 6, 7, 8) to observe the swelling state of the gel under different pH buffer solutions. Multi-component analysis was performed using a low-field nuclear magnetic resonance spectrometer to analyze the water distribution of the gel beads after different pH treatments, and a cryo-scanning electron microscope was used to observe the network structure inside the swollen gel.

[0126] Depend on Figure 2From the c, it can be seen that with the increase of pH, the swelling rate of the hydrogel gradually increases. This is because sodium alginate is dissolved in an acidic solution, and its carboxyl group combines with hydrogen ions to form carboxylic acid. Due to this reaction, hydrogen bonds are formed between carboxyl groups, weakening the hydrogen bonds between carboxyl groups and water molecules, thereby preventing the entry of external water molecules, reducing the rate of SA expansion, and T2 continues to decrease. This is because water penetrates into the interior of the hydrogel, reducing its degree of freedom and slowing down its relaxation rate. Therefore, the swelling rate is inversely proportional to T2. High-viscosity hydrogels change slowly at pH values ​​of 3-6, probably because the greater the viscosity, the greater the degree of cross-linking of the hydrogel, reducing the pH sensitivity of the hydrogel at low pH.

[0127] Depend on Figure 2 d represents the variation of storage modulus (G′) and loss modulus (G″) with frequency. The hydrogel was subjected to dynamic frequency scanning in the angular frequency range of 0.1 to 100 rad / s. When the angular frequency increased from 0.1 to 100 rad / s, both the storage modulus (G′) and the loss modulus (G″) increased slightly, while the value of G′ was always higher than that of G″ ( Figure 2 d), and the high viscosity hydrogel G' is always higher than the low viscosity hydrogel G', showing the excellent stability and mechanical properties of the high viscosity hydrogel. This shows that the prepared hydrogel can firmly lock the internal water, making the T2 measurement value more reliable.

[0128] The above results show that the viscosity of the hydrogel seriously affects the state of water molecules in the hydrogel, and high viscosity sodium alginate is beneficial to the relaxation performance and stability of the hydrogel.

[0129] (3) Expansion dynamics

[0130] The swelling kinetics of the hydrogel beads were determined by measuring the swelling capacity and the results are shown in Figure 3 .

[0131] Figure 3 In a, t / Qt or ln(Q∞ / (Q∞-Qt)) versus time dilation dynamics (LVB); HVB ( Figure 3 c) and t / Qt or ln ( Figure 3 d); (Q∞ / (Q∞-Qt)) versus time dilation dynamics (HVB).

[0132] The swelling rate is fast at the beginning of swelling and gradually decreases to the equilibrium value. From the first-order kinetic model, the swelling rate at a given time is proportional to the remaining available swelling capacity. Therefore, when the equilibrium swelling capacity is Q∞, the swelling capacity at time t is Qt, and the remaining available swelling capacity at time t is Q∞-Qt; the first-order kinetic model can be expressed as:

[0133]

[0134] k1 is the first-order rate constant. Integrating equation (2-1) between the limits of Qt=0, t=0 and Qt=Qt, t=t yields:

[0135]

[0136] The second-order kinetic model is expressed as:

[0137]

[0138] k2 is the second-order rate constant. Integrating equation (2-3) between the limits of Qt=0, t=0 and Qt=Qt, t=t yields:

[0139]

[0140] Will Figure 3 The data in a and c are fitted into equations (2-2) and (2-4), and we get Figure 3 The fitted data are shown in b and d. Regardless of the equilibrium swelling capacity, the data of the low-viscosity hydrogels are consistent with the first-order kinetic model. The results show that the swelling kinetics are determined by the diffusion rate of the solvent in the hydrogel network. In contrast, the data of the high-viscosity gels can be well fitted by the second-order kinetic model. For second-order kinetics, the swelling rate is controlled by the relaxation process of the polymer chains. For materials with high surface areas, such as hydrogels that maintain a porous structure, the effect of the inner boundary area is expected to become more significant. Similar results were found for hydrogels with porous and network morphologies. The degree of relaxation of the polymer chains can control the amount of water entering the hydrogel, thereby more effectively controlling the lateral relaxation time of the system. Therefore, hydrogels with second-order kinetics are more suitable for relaxation sensors.

[0141] In summary, high-viscosity hydrogel beads exhibit greater mechanical strength and magnetic relaxation properties, and are consistent with second-order kinetics.

[0142] (4) Selection and optimization of cross-linking agents

[0143] This experiment compared the gelling effects of two cross-linking agents, calcium chloride and citric acid. The results are shown in Figure 4 Among them, the sample using calcium chloride as the crosslinking agent is the hydrogel of Example 1. A comparative hydrogel is prepared by the same method as Example 1, except that calcium chloride is replaced by citric acid as the crosslinking agent.

[0144] The results are as follows Figure 4As shown in a, when citric acid is used as a cross-linking agent, the swelling of the hydrogel reaches a maximum value when the pH reaches 5. This may be because hydrogen bonds are generated when citric acid is used as a cross-linking agent, and hydrogen bonds are more sensitive to changes in pH. When calcium chloride is used as a cross-linking agent, the melt swelling rate increases steadily with increasing pH. Considering that the pH of the alkaline phosphatase substrate used later is greater than 7, calcium chloride was selected as a cross-linking agent, and the concentration of calcium chloride and cross-linking time were optimized. The results are shown in Figure 4 As shown in b and c, the best effect is achieved when the concentration is 1% and the cross-linking time is 6 hours. The results show that the hydrogel prepared with calcium chloride as the cross-linking agent is more sensitive to pH response.

[0145] (5) Characterization of gel beads

[0146] The SA / CMCS beads prepared in Example 1 were collected, washed several times with deionized water, and freeze-dried for further analysis. The prepared gel beads were subjected to morphological and performance characterization and related tests. The test results are shown in FIG. Figure 5 shown.

[0147] Figure 5 The morphology and size distribution of the gel beads are shown. All beads are milky white, spherical, and uniform in size ( Figure 5 a). Scanning electron microscopy shows that Figure 5 In b, the hydrogel beads have obvious wrinkles, bumps and fibrous surfaces, which are due to the sodium alginate and chitosan polyelectrolyte complex, as well as the alginate monomer and Ca 2+ Cross-linking occurs during diffusion in the microspheres during the curing stage, resulting in water shrinkage and release. The internal structure of the hydrogel beads is porous ( Figure 5 c), after statistical analysis, the internal pore size is mainly distributed in the range of 0.1-0.2μm ( Figure 5 d). However, after freeze-drying, the hydrogel beads changed from spherical to irregular shapes, and their volume decreased significantly ( Figure 5 e), seen under an optical microscope Figure 5 f, the center of the hydrogel bead collapsed and the surface was rough, which usually occurred due to the removal of water during the drying process, resulting in partial collapse of the polymer network. According to BET detection, the voids of the dried gel were distributed within 10 nm.

[0148] To demonstrate the functional groups in the hydrogel beads and the molecular interactions of the hydrogel beads, FT-IR spectroscopy was performed on each material (i.e., CMCS, SA) as well as the hydrogel beads. Figure 5 As shown in h, the characteristic absorption of CMCS appears at 3417 cm -1 (-OH and -NH2 stretching vibration absorption), in SA, the main characteristic peak appears at 3422cm -1 (-OH stretching vibration), 1417cm-1 and 1613cm -1 (-COO - The symmetric and asymmetric stretching vibrations of SA and CMCS were compared. The -COO - The infrared absorption of -OH and -NH2 of CMCS shifts to lower wavenumbers, at 1320 cm -1 In addition, the overlapping absorption peaks of CN stretching vibration and NH bending vibration were observed, proving that there was a strong intermolecular interaction between CMCS and SA, which promoted the formation and structural stability of hydrogel beads. - At 1613cm -1 and 1417cm -1 The characteristic absorption peak at + Ca 2+ Replace with -COO - This proves that the addition of carboxymethyl chitosan can improve the stability of sodium alginate hydrogel and the synthesis of hydrogel beads is successful.

[0149] (6) Sodium alginate concentration

[0150] The hydrogels were prepared by the same method as in Example 1, except that the concentration of sodium alginate (SA) was changed to 1.5% (w / v), 2.0% (w / v), 2.5% (w / v), 3.0% (w / v), 3.5% (w / v), and 4.0% (w / v). The ΔT2 of the hydrogel beads was measured by the same method as in Example 3. The results are shown in Figure 6 .

[0151] The results showed that the best effect could be obtained when the concentration of sodium alginate (SA) was 2.0% (w / v).

[0152] (7) Stability analysis of gel bead T2 signal

[0153] Fe3O4@NPC, as a superparamagnetic material with excellent performance, has been used in the construction of MRS. However, the ferromagnetic Fe3O4@NPC has a high magnetic susceptibility under the magnetic field of the nuclear magnetic resonance instrument, which leads to nonspecific aggregation, resulting in instability of the MRS sensor and may cause false positive results. 2+ / Fe 3+ Transformation to construct T2-based MRS, but due to Fe 2+ It is easily oxidized and will destroy the Fe-based 2+ / Fe 3+In the Gel-MRS of the present invention, the hydrogel itself has no magnetism and will not be affected by the external magnetic field. The hydrogel structure is relatively stable and is not easily affected by the surrounding environment, which can effectively improve the stability of the sensor. In order to verify this stability, this experiment measured the Fe3O4@NPC, Fe 2+ / Fe 3+ The transverse relaxation time of the hydrogel beads of the system and Example 1 under the action of the magnetic field is 5min, 10min, 15min, 20min and 25min. The results are shown in Figure 7 , where A represents the change of T2 value of different materials in an external magnetic field with the placement time; B represents the change of T2 value of different materials at room temperature with the placement time.

[0154] Figure 7 The results of A show that the △T2 value of Fe3O4@NPC fluctuates by 338ms, which is 7.6 times that of hydrogel beads, while Fe 2+ / Fe 3+ The △T2 value of the system fluctuates slightly. The stability of the hydrogel beads is significantly higher than that of Fe3O4@NPC, which verifies the sensor's ability to resist interference from magnetic fields.

[0155] In addition, this experiment also explored the impact of the external environment on the three systems over time. Specifically, the three systems were placed in the natural environment for different periods of time to test the changes in T2. Figure 7 As shown in Figure B, after 1 day, 2 days, 3 days, 4 days, and 5 days, due to the extreme instability of Fe3O4@NPC, the △T2 on the first day was 338.8ms. Due to oxidation, the △T2 value of FeCl2 solution after 5 days reached 338, the △T2 value of FeCl3 solution after 5 days reached 387, while the △T2 of hydrogel beads only changed by 64. The results show that the storage stability of hydrogel beads is also very good.

[0156] Experiment 2 Optimization of relaxation sensing system conditions

[0157] The effects of incubation time (hydrogel bead swelling period) and antibody / antigen concentration on the relaxation sensing system were investigated respectively, and a suitable relaxation sensing system was selected. The method was as described in Example 3.

[0158] The specific method is:

[0159] ① Investigate the effect of incubation time (swelling period of hydrogel beads) on the relaxation sensing system: Under the condition of antibody / antigen concentration of 2 μg / mL, incubate for different time (30, 60, 90, 120, 150, 180, 240 and 360 min), the corresponding intensity of the relaxation sensing system;

[0160] ② Investigate the effect of different antigen / antibody concentrations on the relaxation sensing system: Under the condition of incubation time of 180 min, the response intensity of the relaxation sensing system composed of antigen / antibody of different concentrations (1.0, 2.0, 3.0, 4.0 and 5.0 μg / mL) was tested.

[0161] The optimization results are as follows Figure 8 As shown, when the antigen / antibody concentration in the relaxation sensing system is 4 μg / mL and the incubation time is 180 minutes, the relaxation sensing system is optimal. Figure 8 The horizontal axis of A is the incubation time, Figure 8 The abscissa B is antigen / antibody / concentration.

[0162] Experiment 3: Sensor mechanism analysis

[0163] The hydrogel beads of Example 1 were placed in solutions with pH values ​​of 3.0, 4.0, 5.0, 6.0, 7.0 and 8.0, and their swelling behaviors were observed by low-field nuclear magnetic resonance and cryo-electron microscopy. First, the T2 of the hydrogel beads treated with solutions of different pH values ​​was studied by nuclear magnetic resonance. Fig. 9 As shown in a, gel beads treated with different pH solutions all contain peaks centered at 1-10ms, 100-1000ms, and 1000-10000ms, representing bound water, fixed water, and free water, respectively. The bound water and fixed water are the water inside the gel, and the free water is the water outside the gel. The ratio of internal water to external water is shown in Fig. 9 As shown in Figure b, with the increase of pH, the peak ratio of internal water between 1 and 1000 gradually increases. This is mainly because when the pH is low, the polymer network is in a curled state and cannot accommodate more water molecules. However, with the increase of pH, the suspended -COOH groups in the polymer are replaced by OH - Completely ionized, due to -COO - Due to the electrostatic repulsion between functional groups, the polymer network is fully expanded. Therefore, the polymer network can accommodate relatively more water molecules, and the external water peak (>1000) gradually moves to the left, and its proportion gradually decreases. The results show that as the pH value of the solution increases, the external free water gradually transforms into internal bound water. The signal intensity of the hydrogel was evaluated based on T2-weighted magnetic resonance imaging (MRI). As the pH increases, the relaxation intensity of the hydrogel beads becomes stronger ( Fig. 9 c), which also proves that the water content inside the hydrogel is getting higher and higher.

[0164] Fig. 9 In the figure, a represents water distribution; b represents peak area at different relaxation times; c represents nuclear magnetic resonance imaging; d represents a photograph of the experimental sample; ei represents a low-temperature scanning electron microscope photograph.

[0165] Changes in the state of water molecules in LF-NMR: As the pH value increases, the water content in the gel beads gradually increases. In order to further verify the reliability of the LF-NMR test results, the dried hydrogel beads were immersed in buffer solutions of different pH values, and the internal structure of the hydrogel was detected using a low-temperature scanning electron microscope ( Fig. 9 The size of the hydrogel network in different pH solutions changes greatly: as the pH of the solution increases, the pore size of the gel network gradually expands, which further proves that the gel beads can change the water state by pH stimulation, from external water to internal water, resulting in a decrease in the degree of freedom of water in the system and a decrease in T2.

[0166] Experiment 4 Specificity and stability analysis

[0167] According to the same method as the establishment of the cadmium ion standard curve in Example 3, Cd 2+ Analog Ag + , Na + ,Mg 2+ , Pb 2+ , Zn 2+ , Fe + ,Cu 2+ , Ba 2+ , studied the Gel-MRS sensor for detecting Cd 2+ These analogs and Cd 2+ The concentration was 1 ng mL -1 The test results are as follows: Fig.10 As shown in c, Cd 2+ The group has a significant ΔT2 value signal response. The signal responses of other groups are negligible, indicating that the Gel-MRS sensor constructed in Example 3 is sensitive to Cd 2+ Has specific recognition function.

[0168] The stability of the sensor of Example 2 under external magnetic field conditions was verified in the same manner as in Example 3. -1 The rice was spiked and tested, and the rice was placed in a low-field nuclear magnetic resonance instrument to detect its T2 value after 0, 5, 10, 15, 20, and 25 minutes under external magnetic field conditions, and the recovery rate was calculated. The results are as follows Fig.10 As shown in Figure d, under external magnetic field conditions, the recovery rate of the sensor was between 96.46% and 103.09% without much fluctuation, thus proving that the magnetic relaxation sensor based on sodium alginate gel has excellent stability.

[0169] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0170] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A magnetic relaxation switch sensor, characterized in that: include: Sodium alginate carboxymethyl chitosan hydrogel, cadmium ion specific antigen, cadmium ion specific antibody, alkaline phosphatase labeled secondary antibody, and 2-phospho-l-ascorbic acid trisodium salt.

2. The magnetic relaxation switch sensor according to claim 1, characterized in that: The sodium alginate carboxymethyl chitosan hydrogel is prepared from sodium alginate and carboxymethyl chitosan in a mass ratio of (1.5-4):1, preferably a mass ratio of 2:

1.

3. The magnetic relaxation switch sensor according to claim 1 or 2, characterized in that: The sodium alginate is high-viscosity sodium alginate; Preferably, the ratio of the comonomers β-d-manuronic acid (M) and α-l-guluronic acid (G) of the sodium alginate is (1:1)-(1:2), more preferably 1:

2.

4. The magnetic relaxation switch sensor according to any one of claims 1 to 3, characterized in that: The preparation method of the sodium alginate carboxymethyl chitosan hydrogel comprises: dissolving sodium alginate and carboxymethyl chitosan in water to obtain a blend; adding the blend into a calcium chloride solution for cross-linking to obtain the sodium alginate carboxymethyl chitosan hydrogel; Preferably, the concentration of sodium alginate in the blend is 1.5%-4.0% (w / v), and the concentration of carboxymethyl chitosan is 1.0% (w / v).

5. The method for constructing the magnetic relaxation switch sensor according to any one of claims 1 to 4, characterized in that: include: Providing sodium alginate carboxymethyl chitosan hydrogel; The sodium alginate carboxymethyl chitosan hydrogel, cadmium ion specific antigen, cadmium ion specific antibody, alkaline phosphatase labeled secondary antibody, and 2-phospho-l-ascorbic acid trisodium salt are mixed to obtain a magnetic relaxation switch sensor.

6. The method for constructing a magnetic relaxation switch sensor according to claim 5, characterized in that: The construction method further comprises the step of blocking the cadmium ion specific antigen with bovine serum albumin in advance.

7. Application of the magnetic relaxation switch sensor according to any one of claims 1 to 4 in cadmium ion detection.

8. A method for detecting cadmium ions using the magnetic relaxation switch sensor according to any one of claims 1 to 4, characterized in that: include: The nuclear magnetic resonance imaging analysis method is used to detect and obtain the hydrogen proton transverse relaxation time T2 of the sodium alginate carboxymethyl chitosan hydrogel when no sample to be tested is added; The magnetic relaxation switch sensor is mixed with a sample to be tested; and a nuclear magnetic resonance imaging analysis method is used to detect and obtain the hydrogen proton transverse relaxation time T2' of the sodium alginate carboxymethyl chitosan hydrogel at this time; According to the formula ΔT2=T2'-T2, ΔT2 is obtained; The cadmium ion concentration in the sample to be tested is obtained according to ΔT2 and the standard curve.